Production parameters and profitability of the Egyptian household poultry sector: a survey. Issue 1 (March 2016) - FASINA, F.O.; ALI, A.M.; YILMA, J.M.; THIEME, O.; ANKERS, P.
Abstract : Poultry production has experienced tremendous change in Egypt in the last three decades. Small-scale family poultry production, otherwise termed household poultry, was part of this transformation but to date no concise description has been made of Egyptian household poultry. In this report, this is described using surveys and reviews. Inputs and outputs of this production system were evaluated and the profitability of the household poultry was estimated. Household poultry contribute immensely to food security in Egypt; providing income for individual families. A mean flock size of 73 (mixed breeds) was determined and this yielded a net annual profit of 2287.67LE (US397.34) per annum. The important household poultry diseases are principally viral and bacterial. While Egyptian household poultry are similar to others in Africa in terms of multi-species flocks, women-driven projects, labour and marketing structures, it differs in input systems, hatchery method, disease management, and other indices. Suggestions for improvement of this sector of the poultry industry are offered.